(3GdThGgOs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3YHO Gddg Hf eMeO YHGO s)
(3ChdgG (B:s
(3gPG cJGH jJVef eG jCJ Hg ThGgO GdMb ai GdbdH ef GdYdhe GdEdgjI s
(3BNQgG (B:s
(3ai Mb ef HdZg cdGec hdG jRGd , aEfg CRLi hCQLG hCfLi hGddg CYde s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs